PENYULUHAN IMUNISASI DI POSYANDU DESA BULOK - Anita Noviana; Annisak Meisuri; Idawati; Juni Ekawati; Meichiko Indah; Nita Arena Putri; Nurniyanti; Nylida Sari; Nyimas Evi SMS; Ririn Martina; Tuti Mayati; Tri Widayanti; Nur Alfi fauziah (Kirana Publisher, 2024)
Immunisation protects children against several preventable diseases (PD3I). Immunisation is a highly effective form of health intervention in reducing infant and under-five mortality. Every year more than 1.4 million children worldwide die from diseases that could be prevented by immunisation. Despite the fact that many mothers now bring their babies to health workers for immunisation, only a small proportion of them are given counselling. in bulok village there are still toddlers who do not get complete basic immunisation due to lack of knowledge and hassle. The expected output target is an increase in knowledge between before and after counseling, as well as awareness of mothers to bring their children to Posyandu to get immunised. The method in this Community Service is carried out by providing counseling on Basic Immunisation. In the early stages of counselling, the material provided is about the definition, benefits, and impacts if immunisation is not given to toddlers. The results of this Community Service activity on Counseling on Basic Immunisation for Toddler Mothers at the Bulok Village Posyandu found that participants listened, were enthusiastic, and understood the material presented by the implementer of the extension activities. The results of the service are an increase in knowledge and awareness of mothers to bring their children to get immunised in an effort to prevent disease.